Pulmonary Intravascular Large B‐Cell Lymphoma Diagnosed by Transbronchial Lung Cryobiopsy: A Case Report - Yen Shen Wong; Hideaki Furuse; Yuji Matsumoto; Kenya Sato; Takaaki Tsuchida (Respirology Case Reports)
ABSTRACT Intravascular large B‐cell lymphoma (IVLBCL) is a rare and aggressive extranodal lymphoma characterised by the proliferation of malignant lymphocytes within the lumens of blood vessels. Diagnosing IVLBCL is often challenging due to its nonspecific clinical presentation and difficulty in obtaining histopathologic confirmation. Here, we present a case of IVLBCL diagnosed by transbronchial lung cryobiopsy (TBLC). A 68‐year‐old man was initially diagnosed with diffuse large B‐cell lymphoma based on an orchiectomy specimen. Although initial treatment achieved complete remission, tumour marker levels progressively increased during follow‐up. TBLC was performed after bone marrow biopsy, cerebrospinal fluid cytology, and a random skin biopsy failed to detect lymphoma lesions. Histological findings of the TBLC specimen demonstrated medium‐sized atypical lymphocytes filling the blood vessels, leading to a diagnosis of IVLBCL. Cryobiopsy specimens allow for the evaluation of alveolar structure and microvasculature, making it a valuable and less invasive diagnostic option for pulmonary IVLBCL.